Maquillaje de coronas de zirconio monolítico en el laboratorio dental artículo de revisión - Tubón Yancha, Germán Alexander (2025)
The makeup technique, also known as direct restoration with zirconium oxide, involves a support system called "transformation toughening. This is based on zirconium partially stabilized and exposed to an area of high mechanical emphasis, because it is the top of the tip, undergoing a transformation from a translucent form and converting from tetragonal to monoclinic, achieving a larger volume. In this way, the strength is increased, and the propagation of the crack is avoided. This property gives these porcelains a flexible strength ranging from 1000 to 1500 MPa (megapascals). Zirconium oxide as a material for fixed prosthetics is a good alternative to traditional metal-ceramic restorations. This material is still recommended for dental use today, and with the emergence of CAD/CAM systems, there has been a steady progression in both materials and technologies to achieve the most aesthetic restorations possible. The professional must study each dental case and assess the clinical efficacy of each patient. In conclusion, the makeup technique of monolithic zirconium crowns offers favorable results in both functionality and aesthetics, which is the main goal today, as well as optimal timing to achieve the objective and the operator's competence